2012
DOI: 10.1523/jneurosci.2957-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Affective Neural Plasticity following Active-Controlled Mindfulness Intervention

Abstract: Mindfulness meditation is a set of attention-based, regulatory and self-inquiry training regimes. Although the impact of mindfulness meditation training (MT) on self-regulation is well established, the neural mechanisms supporting such plasticity are poorly understood. MT is thought to act on attention through interoceptive salience and attentional control mechanisms, but until now conflicting evidence from behavioral and neural measures has made it difficult to distinguish the role of these mechanisms. To res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
243
2
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(270 citation statements)
references
References 58 publications
18
243
2
7
Order By: Relevance
“…In line with this prediction, several prior studies have demonstrated that MT can improve performance on measures of selective and sustained attention (e.g., Allen et al 2012;Jensen et al 2012;Jha et al 2007;MacLean et al 2010;Zanesco et al 2013), and WM (Chambers et al 2008;Jensen et al 2012;Mrazek et al 2013;Quach et al 2016;Van Vugt and Jha 2011;Zeidan et al 2010; but see Morrison et al 2014), and can reduce performance lapses associated with mind wandering Morrison et al 2014;Mrazek et al 2013).…”
mentioning
confidence: 71%
“…In line with this prediction, several prior studies have demonstrated that MT can improve performance on measures of selective and sustained attention (e.g., Allen et al 2012;Jensen et al 2012;Jha et al 2007;MacLean et al 2010;Zanesco et al 2013), and WM (Chambers et al 2008;Jensen et al 2012;Mrazek et al 2013;Quach et al 2016;Van Vugt and Jha 2011;Zeidan et al 2010; but see Morrison et al 2014), and can reduce performance lapses associated with mind wandering Morrison et al 2014;Mrazek et al 2013).…”
mentioning
confidence: 71%
“…For example, in a cross-sectional study using Vipassana meditators versus controls, enhanced ACC activation during breath awareness (focused attention) meditation was found [21]. In a longitudinal mindfulness training versus active control, greater dorsolateral PFC activation during emotional Stroop executive processing was detected [22].…”
Section: The Effects Of Mindfulness Meditation On Brain Structures Anmentioning
confidence: 99%
“…The most consistent findings in terms of showing effects of meditation training were amongst studies that examined conflict resolution amongst competing alternatives, such as the Stroop task (e.g. Allen et al 2012;Moore and Malinowski 2009;Teper and Inzlicht 2013). However, other studies examining conflict resolution and inhibitory control show little or no effect of mindfulness training on responses (Stroop: Anderson et al 2007;Moore et al 2012;Flanker: Larson et al 2013).…”
Section: Introductionmentioning
confidence: 84%
“…For example, Stroop trials present both words and colour on every trial and flanker trials present both central target and flanker distractors on every trial (e.g. Anderson et al 2007;Allen et al 2012;Moore et al 2012;Moore and Malinowski 2009;Teper and Inzlicht 2013). The identity of the bivalent stimulus determines whether the trial is congruent or incongruent.…”
Section: Discussionmentioning
confidence: 99%